VD_FINDINFO HC / 2018 / 1094 vom 5. November 2018 - VD Tribunal cantonal (2018)
SUSPENSION DE LA PROCÉDURE, APPEL EN CAUSE, LITISPENDANCE, DEMANDE RECONVENTIONNELLE | 126 CPC (CH), 63 al. 1 CPC (CH), 81 CPC (CH), 85 CPC (CH)